Market segmentation: organizational archetypes and research agendas. - Jenkins, Mark; McDonald, Malcolm H. B. (Emerald, 1997)
The study of how organizations segment their markets has traditionally taken a prescriptive and analytical approach. More recently, a number of academics and practitioners have voiced concerns over the evident gap between how such concepts are viewed in theory and how they are applied in practice. These issues have already been raised in academic papers, but almost entirely at an abstract level. Introduces a more concrete aspect to the debate by proposing a series of organizational archetypes which illustrate how organizations may segment their markets in practice. These archetypes are developed from a series of mini-case studies which provide a basis for understanding how organizations may interface with the market at both an explicit and implicit level. Discusses the implications for both academic research and organizational practice.